The Activation for the Use of Orphan Works in Cultural Facilities: Focusing on the Establishment of Standards for Diligent Search and the Preparation of Compensation Payment Levels - Donghui Kim (Journal of Intellectual Property)
With the establishment of Article 35(4) of the Copyright Act and the relevant regulations within the enforcement decree of the same law, cultural facilities can use Orphan Works without utilizing the previous legal permission system, thus reducing the burden of the system’s procedural fees. The economic burden of cultural facilities was further, and significantly, reduced by newly established regulations stating that compensation did not need to be paid in advance. Consequently, cultural facilities can contribute to cultural development using, indeed increasing their utilization of, the resources within Orphan Works. However, unclear “diligent search” standards set by Presidential Decree and the inability to predict the “level of compensation” when copyright holders appear are new concerns for cultural facilities as they face the limitations and burdens of using the system. The goal of this study was to offer help with these challenges, outlining from a practical point of view the parts of the Copyright Act that require revision and supplementation to operate the current system.